De l’agentivité mythique et incantatoire - Laurent Fontaine (Ateliers d'Anthropologie)
This article presents a new analysis of the myth of Kawáirimi (Jacopin, 1981), based on a second, more detailed version recorded in 2008 from Mario Matapi, a well-known healer, who agreed to explain key passages, linking them to several incantatory verses. On the basis of this comprehensive version of the myth of Kawáirimi transcribed in Yucuna language and then translated, I will present different forms of agency proper to this speech. I will first examine its social context and its effects on today’s Yucuna population, near La Pedrera. Next, I will study the agency strictly internal to the narrative, by proposing a method of exploring the two versions that makes it possible not only to establish a comparative and general table of their principal acts, but also to analyse the effects and repercussions between these acts. Finally, I will analyse incantation extracts that are supposed to work by referring to the story.